2020
DOI: 10.1038/s41598-020-60190-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Genetic Complexity of Fusarium Crown Rot Resistance in Wheat

Abstract: Fusarium crown rot (FCR) is one of the most important diseases of wheat (Triticum aestivum L.). fcRis mainly caused by the fungal pathogens Fusarium culmorum and F. pseudograminearum. In order to identify new sources of resistance to FCR and to dissect the complexity of FCR resistance, a panel of 161 wheat accessions was phenotyped under growth room (GR) and greenhouse conditions (GH). Analysis of variance showed significant differences in crown rot development among wheat accessions and high heritability of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 70 publications
4
19
0
Order By: Relevance
“…Despite the broad awareness of losses caused by F. pseudograminearum, till now no durable resistant cultivars have been released. The absence of sufficient knowledge, technical know-how and limited understanding of the genetic basis have been the key challenges in developing resistant cultivars (Pariyar et al, 2020). FCR characterized by stem base or leaf sheath browning and whiteheads, is a frequent and severe disease in many parts of the semiarid regions worldwide (Chakraborty et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the broad awareness of losses caused by F. pseudograminearum, till now no durable resistant cultivars have been released. The absence of sufficient knowledge, technical know-how and limited understanding of the genetic basis have been the key challenges in developing resistant cultivars (Pariyar et al, 2020). FCR characterized by stem base or leaf sheath browning and whiteheads, is a frequent and severe disease in many parts of the semiarid regions worldwide (Chakraborty et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Major-gene resistance to FCR is poorly understood (Aoki et al, 2014;Kazan & Gardiner, 2018;Pariyar et al, 2020;Smiley et al, 2003) and unavailable at the present time, but there is limited evidence that some wheat cultivars showed reduced FCR severity compared with others (Graebner & Mundt, 2019), possibly indicating a tolerance response. This evidence is based on cultivar trial efforts conducted at a location in Sherman County, Oregon.…”
Section: Introductionmentioning
confidence: 92%
“…Several studies have confirmed that ER Lumenal Hsp70 protein FpLhs1, transcription factor FpAda1, and FpNPS9 are important for F. pseudograminearum infection [12][13][14]. FCR resistance responses in wheat are complex and controlled by multiple quantitative trait loci (QTLs) [15]. Thus, some studies have focused on the identification of gene loci in wheat and barley that are resistant to crown rot [16,17].…”
Section: Introductionmentioning
confidence: 99%